Libya in transition: governance challenges and civil society’s prospects in political and economic reforms - Noureddine Selmi (Global Security: Health, Science and Policy)
This article examines Libya’s complex landscape, marked by a persistently weak state apparatus since the Gaddafi era, which continues to raise significant concerns. Following the 2011 revolution, Libya has remained a battleground of conflict and war. This study investigates the factors influencing Libya’s transition, with a particular focus on the role of civil society in governance and political and economic reforms. The research draws on two qualitative studies that complement the researcher’s expertise in the Libyan context. The first study involved on-site meetings and discussions, while the second included 32 interviews conducted in late 2023 and early 2024. Participants, comprising politicians, economists, academics, and civil society leaders, provided diverse perspectives. Key findings highlight Libya’s lack of strong state institutions and the rule of law, challenges to governance and reforms amid ongoing conflict, and scepticism towards civil society, which makes its role more complex and more difficult. This study offers theoretical perspectives and invaluable information to foster and facilitate civil society engagement in governance and transition. Additionally, it provides recommendations for creating an enabling environment for transition in Libya and countries facing similar conditions, such as those during the Arab Spring.